(untitled) (JURNAL PROTEKSI KESEHATAN, 2024)
Lactic acid bacteria (LAB) are widely recognized for their numerous benefits. Apart from their medicinal properties, they can also serve as additional ingredient in food. Their high acidity is believed to be a plant’s defense mechanism associated with endophytic microbes, which greatly benefit plant growth. Lactic acid bacteria (LAB) can offer advantages to humans and are widely distributed in nature. However, the collection of indigenous lactic acid remains limited, necessitating exploration of lactic acid from Indonesia’s natural environment. This study aims to isolate and identify endophyt bacteria in the leaves of Averrhoa bilimbi (Blimbing wuluh) that potentially serve as sources of LAB. The research employed purposive sampling for sample collection and laboratory experiments. Results revealed that Blimbing wuluh leaves contain endophytic bacteria which have the potential to be lactic acid bacteria, with positive carbohydrate tests result to ferment lactose, sucrose, and glucose. The results of the Lactic Acid Bacteria test were positive on MRSB media and MRSA media. The results of the endophytic bacteria isolation characterization test succeeded in identifying 3 isolates from Blimbing wuluh (Averrhoa blimbii) which had the potential to be Lactic Acid Bacteria (LAB).